2020
DOI: 10.15376/biores.15.4.8909-8924
|View full text |Cite
|
Sign up to set email alerts
|

Organosolv lignin properties and their effects on enzymatic hydrolysis

Abstract: Lignin plays a crucial role in enzymatic hydrolysis of lignocellulosic biomass. To evaluate the correlation between lignin properties and its effects on enzymatic hydrolysis, five organosolv lignins (OLs) were isolated from woody biomass, and their physico-chemical properties and structural features were characterized. The effects of OL addition on enzymatic hydrolysis of microcrystalline cellulose (pure cellulose) were assessed first, which showed their disparate effects. The addition of three OLs increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The α-ethoxylated β-O-4' aryl ethers substructures (A'α) were founded by the correlations at δC/δH 81.0/4.60 ppm, implying the occurrence of α-ethoxylation during the pretreatment. Additionally, the methylene in α-ethoxylated β-O-4' aryl ethers substructures (A'α-CH2CH3) was founded at δC/δH 65.3/3.38 ppm, which confirmed that α-ethoxylation had occurred in β-O-4' linkages (Huang et al 2020). After fractionation, the α-ethoxylated β-O-4' aryl ether substructures still remained in F2 and F4, implying that the lignins with such substructures were dispersed into the fractions during sequential extraction.…”
Section: D-hsqc Nmr Spectramentioning
confidence: 71%
See 1 more Smart Citation
“…The α-ethoxylated β-O-4' aryl ethers substructures (A'α) were founded by the correlations at δC/δH 81.0/4.60 ppm, implying the occurrence of α-ethoxylation during the pretreatment. Additionally, the methylene in α-ethoxylated β-O-4' aryl ethers substructures (A'α-CH2CH3) was founded at δC/δH 65.3/3.38 ppm, which confirmed that α-ethoxylation had occurred in β-O-4' linkages (Huang et al 2020). After fractionation, the α-ethoxylated β-O-4' aryl ether substructures still remained in F2 and F4, implying that the lignins with such substructures were dispersed into the fractions during sequential extraction.…”
Section: D-hsqc Nmr Spectramentioning
confidence: 71%
“…The organosolv process has been demonstrated as an effective technique for the collection of sulfur-free, low molecular-weight lignin with few inorganic impurities (Hamauzu et al 2010;Huang et al 2020). In a previous study, the effect of extraction conditions on auto-catalyzed ethanol organosolv lignin (AEOL) from Chinese quince fruit was assessed, confirming the optimal conditions to collect AEOL with high antioxidant performance (Cheng et al 2020).…”
Section: Introductionmentioning
confidence: 86%